Quantitative Analysis of Heparanase Gene Expression in Normal Cervical, Cervical Intraepithelial Neoplastic, and Cervical Carcinoma Tissues. Issue 9 (1st November 2009) - Varchalama, Eugene; Rodolakis, Alexander; Strati, Areti; Papageorgiou, Theocharis; Valavanis, Christos; Vorgias, George; Lianidou, Evi; Antsaklis, Aristidis
Abstract : Heparanase is an endoglycosidase that specifically cleaves heparan sulfate side chains of heparan sulfate proteoglycans, the major proteoglycans in the extracellular matrix and cell surfaces. Traditionally, heparanase activity was implicated in cellular invasion associated with angiogenesis, inflammation, and cancer metastasis. More recently, heparanase up-regulation was documented in an increasing number of primary human tumors. Ιn this study, we sought to investigate the expression of heparanase messenger RNA (mRNA) in normal cervical tissue and intraepithelial cervical lesion and its clinicopathologic importance in invasive cervical cancer. Gene expression of heparanase was assessed by quantitative real-time reverse transcriptase polymerase chain reaction in 28 normal cervical, 26 intraepithelial neoplastic, and 48 cervical cancer tissue samples. Heparanase mRNA expression was different between the 3 groups and lower in normal cervical specimens in relationship with intraepithelial cervical lesions and invasive cervical cancer tissue samples ( P = 0.048). Gradually increasing expression of heparanase was evident as the cells progressed from low-grade to high-grade squamous intraepithelial lesions ( P = 0.002). In invasive cervical cancer cases, there was a direct correlation between heparanase expression and tumor size ( P = 0.002). In cases treated with radical hysterectomy and pelvic lymphadenectomy, the heparanase mRNA expression was significantly higher in tumors exhibiting lymph vascular space invasion ( P = 0.044) and in cases with big tumor size ( P = 0.005). In our study, we did not find any significant correlation between disease-free and overall survival rates and expression of heparanase ( P = 0.396 and P = 0.712, respectively). The results of this study suggest that the gene expression of heparanase in cervical cancer enhances growth, invasion, and angiogenesis of the tumor and may have therapeutic applications.